THE SOCIETY OF SPECTACLE: AN ISLAMIC PERSPECTIVE - Halim, Hendra; Nisva, Raisa Ullya; Humaira, Radhia (Universitas Syiah Kuala, 2024)
This research explores the relevance of Guy Debord's concept of the